Pengaruh Gaya Kepemimpinan Kepala Sekolah terhadap Kepuasan Kerja Guru Taman Kanak-Kanak (TK) di Kecamatan Bergas - Endarini, Amelia Dian; Kusumaningsih, Widya; Ginting, Rosalina BR. (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
The aim of this research is to determine the magnitude of the influence of the school principal's leadership style on the job satisfaction of Kindergarten (TK) teachers in Bergas District. The population in this study was 114 Kindergarten (TK) teachers in Bergas District, with a sample of 89 people using proportional random sampling techniques. The data collection method used is the questionnaire method. The data analysis used is descriptive analysis, prerequisite tests and simple linear regression analysis. Data were analyzed using the SPSS for Window version 25 program. From the research results, it can be seen that the average score for the teacher job satisfaction variable was 123.58, including the satisfied category, and the average score for the principal leadership style variable was 128.42, including the good category. The prerequisite test results from the research data obtained that the data was normally distributed, homogeneous, linear, not multicollinear, and there was no heteroscedasticity. From the hypothesis test, it was found that there was a positive influence of the principal's leadership style on teacher job satisfaction with the equation Y=14.617+0.916X which had a very strong correlation strength of 0.825. Kindergarten (TK) teachers' job satisfaction is influenced by the school principal's leadership style. The democratic leadership style is applied by involving teachers in every activity at school, respecting each other and giving teachers the opportunity to develop their initiative and creative abilities. Meanwhile, the supportive leadership style in providing support in completing teachers' tasks still needs to be improved. Keywords: Leadership style, Job satisfaction, Kindergarten teachers